Exosomes and pancreatic diseases: status, challenges, and hopes - Guo, Xiao-Yu (Int J Biol Sci, 2019)
Pancreatic disease, including pathologies such as acute pancreatitis (AP), chronic pancreatitis (CP), and pancreatic cancer (PC), is a complicated and dangerous clinical condition involving the disruption of exocrine or endocrine function. PC has one of the highest mortality rates among cancers due to insufficient diagnosis in early stages. Furthermore, efficient treatment options for the disease etiologies of AP and CP are lacking. Thus, the identification of new therapeutic targets and reliable biomarkers is required. As essential couriers in intercellular communication, exosomes have recently been confirmed to play an important role in pancreatic disease, but the specific underlying mechanisms are unknown. Herein, we summarize the current knowledge of exosomes in pancreatic disease with respect to diagnosis, molecular mechanisms, and treatment, proposing new ideas for the study of pancreatic disease.